Gambaran Tingkat Kecemasan Remaja Sekolah Menengah Pertama yang Tinggal di Daerah Rawan Banjir - Susanti Niman; Hanna Tania; Yosi Maria Wijaya (Bulletin of Counseling and Psychotherapy, 2022)
Anxiety is a psychological problem often found in children after the flood. Anxiety experienced can interfere with psychological well-being and academic achievement. The study aimed to determine the prevalence of anxiety levels in junior high school students in flood-prone areas. This study uses quantitative methods and descriptive design with a cross-sectional approach Samples were taken using a total sampling technique of 100 junior high school students living in flood-prone areas. Data were collected using the Screen for Child Anxiety Related Disorders. The results showed that the average age of the respondents was 13.43 years, the standard deviation was 0.756, the minimum age was 12 years, and the maximum period was 16 years. A total of 66.0% of respondents are female. Anxiety descriptions of respondents: 73.0% experienced anxiety disorders, with criteria: generalized anxiety disorder 43%, panic or somatic disorders 54%, separation anxiety 81%, social anxiety 48% and school avoidance 19.0%. Junior high school students who live in flood-prone areas with repeated floods experience anxiety. Based on the study's results, the recommendations require cooperation between counselling teachers and primary health care nurses in charge of school health efforts to screen the psychological health of adolescents affected by floods and provide psychological interventions.